Model of parental involvement and children schooling in Malaysia - Syed Hassan, Sharifah Sariah; Mansor, Norwati; Hashim, Che Noraini (World Research Library, 2015)
Literatures have shown that parental involvement has led to student achievement in schools and their future endeavor. With the innovation of technology and social networks, the world becomes smaller but the relationship between children and parents are at distance. This leads to the investigation in the parental involvement and the extent it affects their children school engagement and goal setting. Using the framework of parental involvement by Epstein and goal setting by Lock and Latham, this study proposed a model where the factor has been extended to religious support as part of the parenting involvement. The study employed a survey of 1624 students from secondary and primary levels from 10 schools derived from four states in Malaysia. A stratified sampling has been addressed to ensure normal distribution of the data. Using AMOS and SPSS for the analysis, a one step structural analysis has been carried out. The model was shown to indicate a good fit model with carefully considerations of deleting insignificant items. The discussion and implications are discussed.